On the Neuroscience of Self-Regulation in Children With Disruptive Behavior Problems: Implications for Education. (December 2016) - Woltering, Steven; Shi, Qinxin
Self-regulation is increasingly recognized as a key predictor of academic and social competence. A multidisciplinary understanding of this ability is timely and can strengthen theory and practice. The present review aims to inform educators on what cognitive neuroscience can teach us about self-regulation. To do so, we will focus on a decade-long research program examining children with disruptive behavior problems and their peers, and ask whether neural measures of self-regulation can (a) covary with individual differences in behavioral measures of self-regulation, (b) trace developmental patterns, and (c) predict or trace behavioral change with successful treatment of disruptive behavior problems. We show that several studies begin to converge on a set of neural measures derived from the prefrontal cortex that can be consistently linked to processes of self-regulation. Next, we will discuss what these measures mean from a cognitive neuroscience perspective and how this knowledge could influence and/or support psychological models relevant to education.